2017
DOI: 10.1021/acs.inorgchem.7b01773
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Chemical Effects of the PtBu2Bridge at Unsaturated Dimolybdenum Complexes Having Hydride and Hydrocarbyl Ligands

Abstract: A high-yield synthetic route for the preparation of the unsaturated anion [MoCp(μ-PBu)(μ-CO)] (2) was implemented, via two-electron reduction of the chloride complex [MoCp(μ-Cl)(μ-PBu)(CO)] (1). Reaction of 2 with [NH][PF] led to the formation of the 30-electron complex [MoCp(H)(μ-PBu)(CO)] (3), in which the hydride ligand adopts an uncommon terminal disposition. DFT analysis of the electronic structure of 3 gave support to the presence of a M≡M triple bond in this complex following from a σδδ configuration, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 68 publications
1
25
0
Order By: Relevance
“…It was then of interest to examine the reactivity of related agostic complexes at even more unsaturated centres, as in the case of the monocarbonyl derivative [Mo 2 Cp 2 (μ‐κ 1 :η 2 ‐CH 3 )(μ‐PCy 2 )(μ‐CO)], which features an agostic methyl ligand bridging over an intermetallic triple bond, but these studies were hampered by the high air‐sensitivity of this molecule. Recently, however, we found that the stability of this type of complex could be significantly improved by using the bulkier P t Bu 2 ligand as support of the dimetal centre . Indeed we found that the targeted methyl complex [Mo 2 Cp 2 (μ‐κ 1 :η 2 ‐CH 3 )(μ‐P t Bu 2 )(μ‐CO)] ( 1 ) could be conveniently prepared in situ upon photolysis of the corresponding dicarbonyl precursor [Mo 2 Cp 2 (μ‐κ 1 :η 2 ‐CH 3 )(μ‐P t Bu 2 )(CO) 2 ] (Scheme ), and this gave us the opportunity to explore in detail its chemical behaviour.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was then of interest to examine the reactivity of related agostic complexes at even more unsaturated centres, as in the case of the monocarbonyl derivative [Mo 2 Cp 2 (μ‐κ 1 :η 2 ‐CH 3 )(μ‐PCy 2 )(μ‐CO)], which features an agostic methyl ligand bridging over an intermetallic triple bond, but these studies were hampered by the high air‐sensitivity of this molecule. Recently, however, we found that the stability of this type of complex could be significantly improved by using the bulkier P t Bu 2 ligand as support of the dimetal centre . Indeed we found that the targeted methyl complex [Mo 2 Cp 2 (μ‐κ 1 :η 2 ‐CH 3 )(μ‐P t Bu 2 )(μ‐CO)] ( 1 ) could be conveniently prepared in situ upon photolysis of the corresponding dicarbonyl precursor [Mo 2 Cp 2 (μ‐κ 1 :η 2 ‐CH 3 )(μ‐P t Bu 2 )(CO) 2 ] (Scheme ), and this gave us the opportunity to explore in detail its chemical behaviour.…”
Section: Methodsmentioning
confidence: 99%
“…Methane elimination again takes place in this case, but also the oxidative addition of the second Si−H bond, to give the hydride silylene derivative [Mo 2 Cp 2 H(μ‐P t Bu 2 )(μ‐SiPh 2 )(CO)] ( 2 ) in high yield . Spectroscopic data for 2 denote the presence of a terminal hydride ( δ H =−5.20 ppm), a semi‐bridging carbonyl (trueν˜ (CO)=1776 cm −1 , δ C =282 ppm) and a bridging silylene ligand ( δ Si =214 ppm), and suggest that the structure of this complex is related to that of the hydride benzylidene complex [Mo 2 Cp 2 H(μ‐P t Bu 2 )(μ‐CHPh)(CO)], an intermediate species detected in the photochemical dehydrogenation of the agostic benzyl complex [Mo 2 Cp 2 (μ‐κ 1 :η 2 ‐CH 2 Ph)(μ‐P t Bu 2 )(CO) 2 ] and studied by DFT methods . Interestingly, compound 2 undergoes a fluxional process, fast on the NMR timescale, that renders equivalent metal centres down to 173 K, likely involving the reversible formation and cleavage of a Si−H bond, which would be analogous to the process computed for the mentioned hydride benzylidene complex.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Isomer 1T coexists in solution with the hydride-bridged isomer when M = W and R = Cy, 3,4 while it is fully dominant when M = Mo and R = t Bu. 5 The representation of the intermetallic interaction for this second isomer is a triple bond under all schemes, including the CBC method.…”
Section: Replymentioning
confidence: 99%